Wild Halophytic Phragmites karka Biomass Saccharification by Bacterial Enzyme Cocktail - Ansari, Immad; Ejaz, Uroosa; Abideen, Zainul; Gulzar, Salman; Syed, Muhammad Noman; Liu, Jing; Li, Wang; Fu, Pengcheng; Sohail, Muhammad (Frontiers in Microbiology, 2021)
Biofuel derived from halophytic biomass is getting attention owing to the concerns of energy versus food crisis. The disadvantages associated with edible bioenergy resources necessitate the need to explore new feedstocks for sustainable biofuel production. In this study, biomass from locally available abundant halophytes (Panicum antidotale, Phragmites karka, Halopyrum mucronatum and Desmostachya bipinnata) was screened for saccharification by an enzyme cocktail comprised of cellulase, xylanase and pectinase from Brevibacillus borstelensis UE10 and UE27, Bacillus aestuarii UE25, Aneurinibacillus thermoaerophilus UE1 and Bacillus vallismortis MH 1. Two types of pretreatment i.e. with dilute acid and freeze-thaw were independently applied to the halophytic biomass. Saccharificatin of acid pretreated P. karka biomass yielded maximum reducing sugars (9 mg g-1) as compared to other plants. Thus, the factors (temperature, pH, substrate concentration and enzyme units) affecting its saccharification were optimized using Central Composite design. This statistical model predicted 49.8 mg g-1 of reducing sugars that was comparable to the experimental value (40 mg g-1). Scanning electron microscopy and Fourier-transform infrared spectroscopy showed significant structural changes after pretreatment and saccharification. Therefore, halophytes growing in saline, arid and semi-arid regions can be promising alternative sources for bioenergy production.